How Values Create Value: Social Capital in Microfinance - The Case of the Philippines - Hans Dieter Seibel; Gilbert Llanto; Benjamin Qui\~nones (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2000)
Values are to a society what character is to a person: it reveals his true inner self, yet is difficult to describe in exact terms. Moreover, a person's character may show in his actions in various, sometimes contradictory ways so that it may be difficult to induce a person's character from his deeds. Asian values, elusive as they are, have been regarded as a cause of the economic rise of a number of Asian countries. Yet some decades earlier, Confucian values were quoted as a cause of underdevelopment of some Asian countries. Has the recent financial crisis also been due to them, in some way, or do we have to wait for economic recovery in order to attribute that to Confucian values? Max Weber, who first studied the impact of values on economic development, was more careful when he presented the results of his research. The Spirit of Capitalism is congruent with the rise of the Protestant Ethic, he said; but he claimed no causal relationship.
Keywords: 330; Mikrofinanzierung; Social Capital; Philippinen